EMPLOYEE LEAVE MANAGEMENT SYSTEM - Adamu, Abubakar (FUDMA JOURNAL OF SCIENCES, 2020)
Employee leave management system combine number of processes and systems to automate and easily manage employee data, leave request, track and grant leave. In many institution staff are entitled to different types of leave, these leave are granted according to institution policy. Administrative department is mostly responsible for managing and granting leave request. To this end, most institution used conventional method of requesting, granting and managing leave. In conventional method, leave is manually request by writing letter to head of department. The head of department minutes and forward the request to higher staff for approval. This method is time consuming, prone to error, require more paper work and difficult to manage. Hence the need for an automated leave management system that is faster, error free, less paper work and easy to manage. The system was achieved by developing an automated employee leave management system using the three tier software architectural model. The System is implemented using web based technologies which include CSS, JS, HTML, MySQL, PHP and runs on Windows operating system. . The overall functionality of the system shows that it work satisfactory and the result obtained shows that the system is error free, faster and allows staff to request for leave in a timely manner. Hence the system can be used by both academic staff and administrative department of an institution for effective and efficient management of employee leave.